A critical evaluation of forensic accounting studies with a view to discerning how practice can be improved to prevent cases of fraud - Alharbi, Abdulrahman Atllah (Journal of Economic, Administrative and Legal Sciences, 2022)
This article provides a critical evaluation of the existing literature that has been developed to date regarding forensic accounting to then discern how the practice could be potentially improved to prevent instances of fraud from arising. To achieve this, this article first provides an understanding of what forensic accounting is and why it is important for preventing instances of fraud. Then, more specifically, this article considers the literature that has been produced in this area about whether and, if so, why there is a need for the practice of forensic accounting to be improved upon to prevent instances of fraud. On this basis, the literature is also evaluated to discern whether any recommendations may be made to prevent instances of fraud from arising in the future and on what basis these recommendations could be made. This is because it is hypothesised that whilst the practice of forensic accounting already achieves a considerable amount regarding the prevention of fraud because of the diverse nature of this kind of work, there is still considerable scope for improvement due to a variety of issues that are considered during this article’s literature review. Finally, this article concludes with a summary of the key points that have been derived from the analysis undertaken regarding the practice of forensic accounting and its potential for improvement to prevent instances of fraud from arising.
Keywords: forensic accounting; fraud; financial reporting misconduct